Directed and On‐Demand Alignment of Carbon Nanotube: A Review toward 3D Printing of Electronics. Issue 4 (2nd January 2019) - Goh, Guo Liang; Agarwala, Shweta; Yeong, Wai Yee
Abstract: Carbon nanotubes (CNTs) are 1D nanostructured materials with unique mechanical, optical, and electrical properties which can be potentially exploited for fabricating wide variety of devices. In addition, the biocompatibility of CNTs makes it attractive for wearable and implantable technology applications. Well‐aligned CNT structures show enhanced properties such as superior electron mobility, strain sensitivity, better mechanical property, and enhanced performance and reproducibility that are absent in their disordered counterparts, thus allowing more promising applications in various fields. With aligned CNTs, devices can be optimized to exhibit better performance with lesser materials and more miniature designs. This review summarizes the landscape of CNTs alignment, either during the growth or post‐growth processing. This paper delineates various CNTs alignment mechanism, process parameters, and challenges of each technique. A comparative discussion on the advantages, disadvantages, and degree of alignment of each technique is presented. A detailed discussion on the various applications that utilize properties of aligned CNTs devices is presented. The advent of 3D printing techniques for printing CNTs for novel and futuristic applications is also discussed. Abstract : This article reviews the state‐of‐the‐art techniques for the alignment of carbon nanotubes comprising both in situ and ex situ techniques. A theoretical background of the driving forces of different technique is presented. Besides, the applications of aligned carbon nanotubes devices are presented. The potential of using 3D printing for printed electronics are also presented and discussed.